Intrinsic motivation as a pathway from gamification to user engagement in mobile tourism apps: A gender moderated model - Hamie, Rola; Ali, Ali Abou; Abbas, Alaa Eldin (Edelweiss Applied Science and Technology, 2026)
This study examines the direct impact of game elements on intrinsic motivation and how intrinsic motivation influences user behaviors, specifically engagement and user-generated content, within tourism and hospitality review platforms. It also investigates gender as a potential moderator in the relationship between game elements and intrinsic motivation. Intrinsic motivation is characterized by psychological needs such as relatedness, autonomy, mastery, and purpose. Findings reveal that game elements positively influence intrinsic motivation, which in turn increases user engagement. Enhanced engagement subsequently leads to more user-generated content. The study further indicates that gender does not significantly moderate the relationship between game elements and intrinsic motivation. These results highlight the importance of motivation-oriented gamification design in digital platforms, as such elements can boost users’ intrinsic motivation and positively affect their behavioral intentions. The research offers practical implications for platform developers and suggests future directions to improve user behavior in Lebanon. It emphasizes the need for strategic gamification approaches to optimize user engagement and content creation within tourism and hospitality review systems.